Prospects for Legal Regulation of Quantum Communication - Minbaleev, A.; Zenin, S.; Evsikov, K. (BRICS law journal, 2024)
The leading countries across the world have entered the race to develop quantum technologies that will enable them to ensure their continued economic prosperity. Among these technologies, a special place is occupied by quantum communication, which is designed to ensure information security in an era where a quantum computer is capable of compromising a number of cryptography algorithms. In this article, this new digital technology includes quantum key distribution and encryption methods that are cryptographically resistant to a quantum computer. The study does not consider the regulation of the quantum communication sub-technology, the so-called “quantum internet,” due to the technical limitations of the existing equipment. The authors note that their predictions about the cryptographic strength of encryption algorithms are based solely on modern knowledge about the capabilities of quantum computing and do not take into account its hidden potential, for example, in terms of cryptanalysis information systems based on a machine learning model generated by a quantum computer. Currently, the only data protection system that is not subject to quantum threats is the technology of quantum key distribution. In today’s information and digital age, information security systems are an important element of critical infrastructure. Given the importance of these technologies, different states use different methods to regulate this field. This article puts forward and substantiates the hypothesis that the implementation of a combination of regulatory legal acts could have a greater positive impact on the development of quantum communication and ensure an acceptable level of information security in the post-quantum era. The analysis showed that a significant number of states and interstate associations are conducting research in this area, relying only on investment growth. This strategy has prevented any country from achieving the competencies of the People’s Republic of China. The authors also analyzed the methods of legal support used by China, Russia, and other countries in the field of quantum communication, which made it possible to identify a model of legal regulation of quantum communication that stimulates this technology’s development.